2013
DOI: 10.1080/00029157.2012.723284
|View full text |Cite
|
Sign up to set email alerts
|

When the Bough Breaks: Rethinking Treatment Strategies for Perinatal Depression

Abstract: Awareness of depression among OB-GYN physicians has increased with the result that more than 13% of pregnant women in the United States receive prescriptions for antidepressant medications. But the safety and effectiveness of these compounds has been exaggerated while the effectiveness of psychotherapy has been overlooked and distorted and various medical guidelines for treatment of perinatal depression have been downplayed or ignored. This article addresses the common fears and misconceptions surrounding trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 209 publications
0
4
0
Order By: Relevance
“…A survey of expectant fathers confirmed that a significant proportion of men worry about their capacity to adequately support their partner, “losing” their partner to the baby, and maintaining closeness [ 29 ]. Rosenquist [ 35 ] argues that although partners are encouraged to monitor and recognize symptoms of depression, this needs to be supplemented with an understanding of how to provide support.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of expectant fathers confirmed that a significant proportion of men worry about their capacity to adequately support their partner, “losing” their partner to the baby, and maintaining closeness [ 29 ]. Rosenquist [ 35 ] argues that although partners are encouraged to monitor and recognize symptoms of depression, this needs to be supplemented with an understanding of how to provide support.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies estimate depression prevalence during pregnancy in the range of 8–16% (Bowen et al, 2012; Colvin et al, 2013). Antidepressant medication is reported to be prescribed to more than 13% of pregnant women in the United States (Rosenquist, 2013), and El Marroun et al (2012) found that 8.7% of 7027 pregnant women studied had clinically relevant depressive symptoms, with 15% of those women receiving selective serotonin re-uptake inhibitors (SSRIs) to relieve depression symptoms during pregnancy. Notably, the prevalence of suicidality in a prospective study of 1,066 women was found to be 6.9–12.0% during the last six antepartum months (Mauri et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This is especially important because antidepressants are now the first line of treatment in the perinatal period, and usage rates are increasing worldwide (Bakker, Kölling, van den Berg, De Walle, & De Jong van den Berg, 2008). There is disagreement about the effects of psychotropic drugs in both the antenatal and the postnatal periods with concerns about them passing through the placenta and also into breast milk, thereby posing possible side effects for both mother and baby (Galbally, Lewis, Lum, & Buist, 2009; Rosenquist, 2013). The literature on antenatal antidepressant effects and antidepressant usage while breastfeeding is inconclusive as to whether the antidepressants or the untreated depression is worse for the fetus/infant (Field, 2008).…”
Section: The Need For Transactional Analysis Researchmentioning
confidence: 99%
“…These were seen as distinct and were deemed to occur postnatally, with the biomedical determinants thought to be either hormonal dysregulation or abnormalities in the hypothalmic-pituitary-adrenal (HPA) axis (Meltzer-Brody, 2011). However, this does not explain perinatal depression in fathers (Ballard, Davis, Cullen, Mohan, & Dean, 1994; Paulson & Bazemore, 2010; Paulson, Dauber, & Leiferman, 2006; Pinheiro, Magalhaes, Horta, da Silva, & Pinto, 2006; all cited in Rosenquist, 2013) or adoptive parents (Payne, Fields, Meuchel, Jaffe, & Jha, 2010; Senecky et al, 2009; all cited in Rosenquist, 2013). Postnatal depression is viewed by the medical profession as one of the most common complications of childbirth (Robertson, Celasun, & Stewart, 2003), and one of the strongest predictors of postnatal depression is depression during pregnancy (Milgrom et al, 2008; O’Hara & Swain, 1996).…”
mentioning
confidence: 97%